The Concept of Strategic Leadership in Strengthening Indonesia's National Defense Resilience in Facing Hybrid Warfare Threats - Edmund Gultom; Asep Adang Supriyadi; Sundring Pantja Djati; Prijanto Prijanto; Sri Sundari (PT Keberlanjutan Strategis Indonesia, 2026)
Changes in the international security environment marked by the spread of hybrid warfare require Indonesia to have strategic leadership capable of integrating military and non-military dimensions in strengthening national defense resilience. This article aims to examine the role of strategic leadership in strengthening Indonesia's defense resilience in the face of hybrid warfare threats. This study uses a descriptive qualitative approach based on a conceptual review and library study of academic literature, as well as official Indonesian government policy documents. The results of the study map the conceptual ambiguity between hybrid threats and hybrid warfare, the operational dimensions of hybrid threats in the maritime, information, and extremism domains, strategic leadership competencies in managing defense capabilities and complexity, and Indonesia's strategic leadership position in Indo-Pacific regional defense diplomacy, ranging from multilateral exercises to ASEAN strategic partnerships. This study concludes that strengthening Indonesia's defense resilience requires five pillars of strategic leadership: conceptual clarity, capability-based leadership, cooperative diplomacy, ethical-resilient leadership, and institutional learning-based leadership. Based on these findings, this article recommends the development of a doctrinal framework that differentiates hybrid threats and hybrid warfare, reforming defense acquisition strategies towards selective self-reliance, strengthening multilateral defense diplomacy, developing an ethics-based strategic leadership program for Indonesian defense officers and officials, and establishing a permanent coordination forum across ministries and institutions.